2018
DOI: 10.3390/molecules23030539
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Degradation of Nitrosamines via Aqueous-Phase UV Photolysis or a UV-Based Advanced Oxidation Process: Quantum Mechanical Calculations

Abstract: Nitrosamines are a group of carcinogenic chemicals that are present in aquatic environments that result from byproducts of industrial processes and disinfection products. As indirect and direct potable reuse increase, the presence of trace nitrosamines presents challenges to water infrastructures that incorporate effluent from wastewater treatment. Ultraviolet (UV) photolysis or UV-based advanced oxidation processes that produce highly reactive hydroxyl radicals are promising technologies to remove nitrosamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is noteworthy that as the quasi-steady state concentration of the chlorine radical is 6–7 magnitudes lower than that of the dichloride radical anion (Figure S10) and that of the carbonate radical (Figure S11), it is unlikely that the chlorine radical contributes significantly to NDMA degradation. In fact, we can estimate that the activation energy for all elementary reactions of the chlorine radical and NDMA (addition to the N atoms, hydrogen abstraction from the methyl groups) is higher than that of their equivalent elementary reactions with the hydroxyl radicals. , Consequently, the aggregate bimolecular reaction rate constant of the chlorine radical with NDMA must be lower than that of its equivalent reaction with the hydroxyl radical (Table , reaction 10).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that as the quasi-steady state concentration of the chlorine radical is 6–7 magnitudes lower than that of the dichloride radical anion (Figure S10) and that of the carbonate radical (Figure S11), it is unlikely that the chlorine radical contributes significantly to NDMA degradation. In fact, we can estimate that the activation energy for all elementary reactions of the chlorine radical and NDMA (addition to the N atoms, hydrogen abstraction from the methyl groups) is higher than that of their equivalent elementary reactions with the hydroxyl radicals. , Consequently, the aggregate bimolecular reaction rate constant of the chlorine radical with NDMA must be lower than that of its equivalent reaction with the hydroxyl radical (Table , reaction 10).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In fact, we can estimate that the activation energy for all elementary reactions of the chlorine radical and NDMA (addition to the N atoms, hydrogen abstraction from the methyl groups) is higher than that of their equivalent elementary reactions with the hydroxyl radicals. 41,42 Consequently, the aggregate bimolecular reaction rate constant of the chlorine radical with NDMA must be lower than that of its equivalent reaction with the hydroxyl radical (Table 1, reaction 10).…”
Section: Environmental Science and Technology Lettersmentioning
confidence: 99%
“…Previous studies have shown that NDMA destruction by Fenton's reagent is most efficient at low pH. Minakata [34] et al proposed that NDMA has three potential initial degradation mechanisms: (i) H atom abstraction from a C−H bond of the methyl group, (ii) HO· addition to amine nitrogen, and (iii) HO· addition to nitrosyl nitrogen. …”
Section: Resultsmentioning
confidence: 99%
“…QMC approach may support experimental data by calculating the reaction energy using statistical thermodynamics. 13 Hence, the aims of this study were to develop and validate a stability-indicating method by high-performance liquid chromatography with diode-array detection (HPLC-DAD) and to evaluate the stability of RN104 in a forced degradation study under different conditions (acidic, alkaline and neutral hydrolysis, oxidation, photolysis and thermolysis). In addition, we proposed the chemical structures of the DP formed in the forced degradation studies.…”
Section: Introductionmentioning
confidence: 99%